Los problemas desigualitarios de la teoría de la justicia de John Rawls. Una mirada desde Hannah Arendt - Benente, Mauro (2011)
In the present article I will analyze thoroughly the justice principles sketched\nby the American philosopher John Rawls and I will indicate the critics advanced\nfrom equalitarian perspectives mainly by Ronald Dworkin, Amartya Sen and Gerald\nCohen. Finally, I will introduce the possible objections that could be made to Rawls?\ntheory from Hannah Arendt?s work which donnot point at the goods distribution criteria\nbut to the idea that conceives society as a closed system